Where are we now? The State of Self-employment and Entrepreneurship for People with Disabilities in Indonesia - Dissa Syakina Ahdanisa (Indonesian Journal of Disability Studies, 2019)
There are more entrepreneurs from the community of people with disabilities than people without disabilities in Indonesia. However, many are working in informal sector, which lead to lower income gain. As a country that has ratified CRPD, Indonesia is required to promote entrepreneurship and self-employment among people with disabilities while ensuring equal opportunity to participate in employment. What has been done so far? How has the condition changed since CRPD ratification in 2011? What are the challenges faced by entrepreneurs with disability in Indonesia? This paper presents a review of existing literature to understand the current state of research on self-employment and entrepreneurship of people with disabilities in Indonesia. The review suggests that national and regional law created to ensure promotion of entrepreneurship for people with disabilities have not yet been implemented optimally.